WAYS OF ARMENIAN AND RUSSIAN TEENAGERS TO OVERCOME INTERCULTURAL COMMUNICATIVE DIFFICULTIES - Samokhvalova, A.G. (Modern Psychology, 2019)
The article presents the results of the study of communicative difficulties experienced by Armenian (n = 50; M = 13.9) and Russians (n = 50; M = 14.1) adolescents aged 13–15 years in situations of intercultural communication. The sociocultural differences of communicative difficulties and ways to overcome them are revealed. Constructive ways of overcoming communicative difficulties (finding a solution to a problem, social support, changing activities, correcting one’s own mistakes, positive reappraisal) and non-constructive (manipulation, aggression, bullying, cyberbulling, false self-destructive behavior) are described. The resources that help Armenian and Russian adolescents overcome difficulties arising in intercultural dialogue are characterized.